Diversification of Vegetable Chip Products in the UP2K Group to Increase Income in Kondangjaya Village - Ekalia Yusiana; Siti Maryani; Suroso; Ana Melani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Vegetable cultivation is one of the efforts made by the UP2K group to optimize the fulfillment of household food needs, and it is the flagship program of Kondangjaya Village to optimize village resources. Vegetables are an important commodity households need to meet their daily food needs. One of the problems with vegetables is that they are easily damaged, therefore it is necessary to process vegetable products into food chips with high economic value. The purpose of the service is to make various vegetable chip products to create products with high economic value, in addition to increasing the knowledge and skills of the UP2K group in making various chip products to help increase household income. The implementation method used starts with preparation, socialization, training, to mentoring of the UP2K group. The result of implementing this service is that the women farmer group is able to increase the knowledge and skills of partners, namely the UP2K group, in utilizing vegetable commodity products to diversify high economic value chip products, as well as being able to increase the knowledge and skills of the UP2K group in making product diversification, namely oyster mushroom chips, spinach chips, bitter melon chips and betel leaf chips.